Reaffirming the Importance of Retroviral Therapy to Prevent Vertical Transmission of HIV: A Case Report [8F]. (May 2016) - Takeshige, Takeko; Rezai, Shadi; Bemis, Thomas; Mercado, Ray; Takeshige, Umeko; Henderson, Cassandra
Abstract : INTRODUCTION: HAART is an undisputed essential tool to preventing vertical transmission of human immunodeficiency virus (HIV). However, there remain missed opportunities to perinatal HIV transmission. We present a case demonstrating perinatal outcome associated the clinical evolution of HIV screening and treatment. METHODS: Case Report. RESULTS: Case: A 19-year-old female with congenital HIV infection presented to our institution at 36 wks gestation having received no prenatal care. On presentation, the HIV viral load was 21, 000 copies/mL and CD4 cell count was 132. At 38 weeks of gestation, after intrapartum administration of Azidothymidine, a primary cesarean was performed. At no time during the antenatal period did the patient use any antiretroviral therapy. Vertical transmission occurred, for which the neonate was treated with, AZT and lamivudine. Upon discharge, the mother discontinued the infant's antiretroviral therapy. The baby's death at age 1 month was attributed to sudden infant death syndrome. During the second pregnancy the patient got adequate prenatal care services that included treatment with Truvada, Abacavir, Mepron, and Kaletra. At 38-weeks of gestation, preoperative and intraoperative AZT was administered for a repeat cesarean that resulted in delivery a neonate with a negative HIV screen. After 3 negative HIV tests, HAART therapy for this patient's second child was discontinued. The patient died 2 years after her second delivery as a consequence of HIV related pneumonia and respiratory failure. CONCLUSION: This case serves to illustrate for patients and health care providers the significant advances in our knowledge regarding HIV vertical transmission and the value of perinatal administration of antiretroviral therapy.